2017
DOI: 10.3390/f8020052
|View full text |Cite
|
Sign up to set email alerts
|

Soil Erosion Risk Assessment in Uganda

Abstract: Land use without adequate soil erosion control measures is continuously increasing the risk of soil erosion by water mainly in developing tropical countries. These countries are prone to environmental disturbance due to high population growth and high rainfall intensity. The aim of this study is to assess the state of soil erosion by water in Uganda at national and district levels, for various land cover and land use (LCLU) types, in protected areas as well to predict the impact of support practices on soil lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(116 citation statements)
references
References 41 publications
3
90
1
Order By: Relevance
“…Previous studies indicated that the rates of soil erosion are generally different for various types of LULC [54][55][56]. Related to this, the surface areas that are not prone to soil erosion, such as urban areas, bare rocks, glaciers, wetlands, lakes, rivers, inlands waters and marine waters [54,57], were not considered in this study.…”
Section: Land Use/land Cover (Lulc) Of Rwandamentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies indicated that the rates of soil erosion are generally different for various types of LULC [54][55][56]. Related to this, the surface areas that are not prone to soil erosion, such as urban areas, bare rocks, glaciers, wetlands, lakes, rivers, inlands waters and marine waters [54,57], were not considered in this study.…”
Section: Land Use/land Cover (Lulc) Of Rwandamentioning
confidence: 99%
“…Previous studies indicated that the rates of soil erosion are generally different for various types of LULC [54][55][56]. Related to this, the surface areas that are not prone to soil erosion, such as urban areas, bare rocks, glaciers, wetlands, lakes, rivers, inlands waters and marine waters [54,57], were not considered in this study. Therefore, the LULC maps of Rwanda for 2000 and 2015 ( Figure 2) provided by the Regional Centre for Mapping of Resources for Development (RCMRD) [58] at 30 m resolution were used to separate erosion-prone (forestland, grassland and cropland) and non-erosion prone areas (wetland, water bodies and built-up) in ArcGIS.…”
Section: Land Use/land Cover (Lulc) Of Rwandamentioning
confidence: 99%
See 3 more Smart Citations